2019
DOI: 10.1007/s10654-018-0476-7
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and labour market participation: a prospective cohort study of transitions between work, unemployment, sickness absence, and social benefits

Abstract: The aim of this study was to investigate the association of alcohol consumption and problem drinking on transitions between work, unemployment, sickness absence and social benefits. Participants were 86,417 men and women aged 18–60 years who participated in the Danish National Health Survey in 2010. Information on alcohol consumption (units per week) and problem drinking (CAGE-C score of 4–6) was obtained by questionnaire. The primary outcome was labour market attachment. Information on labour market attachmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 55 publications
0
45
1
3
Order By: Relevance
“…It is well established that indirect costs, such as non‐employment, constitute a large part of the total economic burden caused by mental disorders . Most previous studies have also shown that most disorders are associated with lower rates of employment and low income , but not necessarily with low education . To our knowledge, the current study is one of the largest to examine the associations of serious mental disorders with subsequent economic outcomes and the first one to compare the associations between different mental disorders that are critical for policy decisions to allocate the healthcare resources to the treatment of these conditions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is well established that indirect costs, such as non‐employment, constitute a large part of the total economic burden caused by mental disorders . Most previous studies have also shown that most disorders are associated with lower rates of employment and low income , but not necessarily with low education . To our knowledge, the current study is one of the largest to examine the associations of serious mental disorders with subsequent economic outcomes and the first one to compare the associations between different mental disorders that are critical for policy decisions to allocate the healthcare resources to the treatment of these conditions.…”
Section: Discussionmentioning
confidence: 95%
“…Cross‐sectional and longitudinal studies have shown that substance abuse disorders, schizophrenia and other psychoses, depression and anxiety disorders are each significantly associated with higher unemployment and lower income over time . It also seems that these associations are stronger for serious mental disorders .…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Moreover, women affected by economic loss showed increased alcohol consumption, whereas men showed increased intoxication, drinking consequences, and alcohol dependence. 27,28 According to Nielsen, in U.S. alcoholic beverage sales shot up sharply from 26.4% in the second week of March 29 to 55% in the third week of March, compared to the same time a year ago, and then downturn and plateau level was observed (22-27.4%). 17,30 Spikes in alcohol sales as stay-at-home orders in the U.S. were being enacted across the country last month, along with survey results suggesting a troubling tendency toward at-home drinking during work hours, indicate a high probability that some lower-risk drinkers could move into a higher-risk category.…”
Section: Discussionmentioning
confidence: 99%
“…Regular alcohol use impairs inhibition and judgment (Lee & Snape, 2008 ), which could result in socially undesirable behavior or other forms of social dysfunction, diminishing the likelihood to acquire or retain daytime activities. This is supported by a prospective cohort study in adults relating high alcohol consumption and problem drinking to adverse labor market transitions, such as a lower chance on finding a new job after being unemployed as well as a higher chance of becoming unemployed (Jørgensen et al, 2019 ). Similarly, another study in young university students found an association between high levels of alcohol consumption and low academic performance as well as low mental health outcomes (Tembo, Burns, & Kalembo, 2017 ).…”
Section: Discussionmentioning
confidence: 91%